Factors Associated with the Usefulness of Public Health Communication in the Context of COVID-19: Lessons Learned from the African, Caribbean, and Black Communities in Ottawa, Ontario - Josephine Etowa; Bishwajit Ghose; Egbe Etowa; Charles Dabone; Malemo Luc; Amoy Jacques; Susan Roelofs; Ubabuko Unachukwu; Danielle Brown-Shreves; Glory Osandatuwa; Haoua Inoua (MDPI AG, 2023)
Public health communication is critical for promoting behaviours that can prevent the transmission of COVID-19. However, there are concerns about the effectiveness of public health communication within Canada's African, Caribbean, and Black (ACB) communities. In the community sample of ACB people in Ottawa, Ontario, we asked community members if they perceive public health message related to COVID-19 to be effective. Using this question, the current study aimed to explore factors associated with the perceived usefulness of public health messages related to COVID-19. Results from the multivariate analysis have shown that ACB people with lower levels of risk perception for COVID-19 were less likely to perceive that public health messages were useful (OR = 0.405, p < 0.01). In addition, mistrust in government COVID-19 information was also negatively associated with their perception that health messages are useful (OR = 0.169, p < 0.01). For socioeconomic status, ACB people with no high school diploma (OR = 0.362, p < 0.05) and income dissatisfaction (OR = 0.431, p < 0.05) were less likely to report the perceived usefulness compared to those with a bachelor's degree and income satisfaction. Based on these findings, we discussed implications for policymakers and directions for future research.